Cognitive Predictors of Cousin Marriage Among Couples Visiting Counseling Centers in Kohgiluyeh-Boyer Ahmad Province - Mari Ataee; Kambiz Karimzadeh-Shirazi; Touraj Ahmadi-Jouybari; Behzad Karami-Matin; Abbas Aghaei; Fazel Zinat-Motlagh* (Hamadan University of Medical Sciences, 2014)
Background and Objectives: Giving birth to a child with disabilities is two-three times more likely in consanguineous marriages. Due to the various negative consequences of such marriages, this study aimed to determine the cognitive predictors of consanguineous marriages. Materials and Methods: In this cross-sectional study, convenience sampling was applied to select 516 people who visited four different marriage counseling centers in Kohgiluyeh-Boyer Ahmad Province. A self-report questionnaire was administered to collect data. Bivariate correlations and logistic regression analysis were performed to analyze the data in SPSS-20. Results: The mean age of the respondents was 23.43 ± 3.96 years (range: 15-30 years). About 43.4% of the participants had married a relative. Regression analysis suggested subjective norms (OR = 1.304) and cultural factors (OR = 1.244) as the best predictors of cousin marriage. Conclusion: Considering the high rate of cousin marriage in the studied population, it is pre-marriage genetic counseling seems essential. Designing educational interventions on subjective norms and cultural factors related to cousin marriage may also be useful in reducing the rates of cousin marriages.